HUBUNGAN ANTARA KEADILAN ORGANISASI TERHADAP KEPUASAN KERJA PADA ANGGOTA SATUAN SAMAPTA POLRES SALATIGA - Alice Zellawati; Avin Yogareza Ryandika; Brigitan Argasiam (IMAGE, 2021)
Job satisfaction for police officers is a very important factor because the satisfaction they obtain also determines a positive attitude towards work and this is influenced by a sense of organizational justice. The aim of this research is to empirically test and analyze the relationship between organizational justice and job satisfaction. The job satisfaction variable is measured using a Likert scale which is based on aspects of job satisfaction, namely job security, opportunities for advancement and development, salary, working conditions, and communication. The organizational justice variable is measured using a Likert scale which is based on two aspects of leadership, namely distributive justice, procedural justice, interactional justice which consists of two components, namely interpersonal justice and information justice. The population in this study was members of the Salatiga Police Samapta Unit, totaling 120 people, using a saturated sampling technique / census technique. The results of this research prove that there is a positive and very significant correlation between organizational justice and job satisfaction as shown by the correlation value rs = 0.816 (p < 1%), the coefficient of determination is 59.9% and the remaining 40.1%. Keywords: Job satisfaction, organizational justice